FRI0328 A Multicenter, Randomized, Double-Blind, Phase 2 Study to Evaluate the Effect of Febuxostat Versus Placebo on Joint Damage in Hyperuricemic Subjects with Early Gout. (9th June 2015) - Dalbeth, N.; Saag, K.; Palmer, W.; Choi, H.; Li, C.; MacDonald, P.; Thienel, U.; Gunawardhana, L.
Abstract : Background: Current guidelines recommend initiating urate-lowering therapy (ULT) in people with gout who have experienced ≥2 acute flares within the past year. However, no clinical trials investigating the early stages of gout and the potential benefits of initiating ULT in early gout had been available. Objectives: The aim of this study was to assess the effect of treatment with febuxostat over a two year period on joint damage by imaging assessments in hyperuricemic subjects with early gout compared to placebo. Methods: In this phase 2, double-blind, multicenter study, 314 adults with early gout and naïve to ULT were randomized to receive either placebo or febuxostat (titrated from 40 to 80mg to achieve sUA <6.0 mg/dL) daily for 2 years. Early gout was defined as a history of ≤2 (1 or 2) flares, and not more than one flare in any 12-month period. All subjects were required to have a serum urate (sUA) level ≥7.0 mg/dL. No subjects were flaring at the time of randomization. The primary affected joint was defined as the location of the first gout flare. The primary endpoint was the mean change from baseline (CFB) in the modified Sharp-van der Heijde (SvdH) erosion score in the plain radiographs (XR) of the primary affected joint (range: 0 to 10). Secondary endpoints included the mean CFB in the total modified SvdH XR score (erosion and narrowing in the hands and feet, range: 0 to 528), and mean CFB in the rheumatoid arthritis magnetic resonance imaging score (RAMRIS) for erosion (range 0-20), bone marrow oedema (range 0-6) and synovitis scores (range 0-3) in the primary affected joint. Synovitis was scored using contrast-enhanced MR images. Results: Subjects were 92% male, 76% white, with a mean age of 51 years and mean sUA of 8.8 mg/dL. sUA levels after two years were 8.2 mg/dL in the placebo group, and 5.7mg/dL in the febuxostat group. At baseline, the mean SvdH XR erosion scores in the primary affected joint was 0.11 in the placebo group and 0.16 in the febuxostat group, with mean CFB of 0.01 in both groups over two years (p=0.47). There was no significant difference between the placebo and febuxostat groups in the change in total modified SvdH XR score or in the RAMRIS erosion or bone edema score (Table ). Mean RAMRIS synovitis scores were 1.09 in placebo and 1.29 in the febuxostat group at baseline. A greater reduction in synovitis score was observed in the febuxostat group (-0.43) at two years, compared with placebo (-0.07, p<0.001). Treatment emergent adverse events (TEAEs) were observed in 73% of participants in each treatment group, with serious TEAEs in 11 (7.0%) placebo and 13 (8.3%) febuxostat subjects. Conclusions: Synovitis is a frequent feature of early gout. In this first clinical trial of subjects with early gout, ULT using febuxostat led to a significant reduction in synovitis over two years of therapy. In contrast, there was no change in erosion with or without ULT during the two year period. This clinical trial is the first to demonstrate that ULT can improve synovitis in patients with gout. Acknowledgements: This study was sponsored by Takeda Pharmaceuticals, Deerfield, IL, USA Disclosure of Interest: N. Dalbeth Grant/research support from: Takeda Pharmaceuticals, Teijin, Menarini, Savient, Ardea Biosciences, AstraZeneca, Metabolex, Pfizer, and Fonterra., K. Saag Grant/research support from: Takeda Pharmaceuticals, Crealta, and Ardea/Astra Zeneca, W. Palmer: None declared, H. Choi Grant/research support from: Astra-Zeneca and Takeda Pharmaceuticals, Consultant for: Astra-Zeneca, C. Li Employee of: Takeda Pharmaceuticals, P. MacDonald Employee of: Takeda Pharmaceuticals, U. Thienel Employee of: Takeda Pharmaceuticals, L. Gunawardhana Employee of: Takeda Pharmaceuticals